ENVIRONMENTAL MANAGEMENT ACCOUNTING, GREEN INNOVATION, AND ENVIRONMENTAL PERFORMANCE IN BATIK MSMES - Utami, Cahyaning Fitri Wulan; Wardani, Marita Kusuma (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
This study examines how environmental management accounting (EMA) contributes to improved environmental performance, particularly among SMEs in developing economies. Moving beyond identifying direct relationships, it explores the mechanism through which this influence occurs. Drawing on the Natural Resource-Based View and Stakeholder Theory, the study investigates both the direct effect of EMA on environmental performance and its indirect effect through green innovation among Batik MSMEs in the Surakarta Residency. A quantitative approach was employed, with data collected from 60 owners and managers and analyzed using PLS-SEM to test direct and mediating relationships. The results indicate that EMA has a positive and significant effect on environmental performance. In addition, EMA encourages green innovation, which further enhances environmental outcomes. These findings highlight green innovation as a key mechanism through which internal accounting practices are translated into tangible environmental improvements. Theoretically, the study integrates the Natural Resource-Based View and Stakeholder Theory by framing EMA as a strategic internal capability that enables firms to address stakeholder expectations through innovation. Empirically, it provides evidence from an emerging economy context and offers practical insights for SME managers aiming to achieve sustainable competitive advantage.